Knowledge, risk assessment, practices, self‐efficacy, attitudes, and behaviour's towards venous thromboembolism among nurses: A systematic review - Khalid Al‐Mugheed; Nurhan Bayraktar (Wiley, 2023)
Abstract Aim This study reviewed the literature on nurses' knowledge, risk assessment practices, self‐efficacy, attitudes, and behaviours towards venous thromboembolism (VTE). Design A systematic review following PRISMA guidelines. Methods CINAHL (via EBSCO), MEDLINE (via PubMed), and Web of Science were electronic databases used to find studies published from 2010 to November 2020 in English language. A Hoy critical appraisal checklist was used to assess the risk of bias and methodologic quality. Results This study included fourteen studies conducted on 8628 Registered Nurses. Nine of the fourteen studies examined nurses' general knowledge level regarding VTE, and five showed that most nurses had a good knowledge of VTE. Of the 14 studies, six assessed nurses' risk assessment knowledge regarding VTE, and three showed that nurses had low knowledge of VTE risk assessment. Eleven studies assessed nurses' practices concerning VTE prophylaxis; 5 of the 11 studies reported that nurses had poor and unsatisfactory levels of VTE practice. Three of the 14 studies showed that nurses had low self‐efficacy and varied beliefs. The most frequent recommendations were to create continuous educational programs and in‐service training programs (n = 11), followed by creating institutional protocols standardizing VTE (n = 6). Conclusions Comprehensive educational programs and campaigns based on well‐established and standardized tools should be provided to nurses to improve their VTE knowledge.